Intellectual Capital and Bank Performance in GCC: A Comparison of Islamic and Conventional Banks - Al Ahmed, Alshammy; Aloutaibi, Shidiqqu (Advances in Accounting Innovation, 2025)
Purpose – Thus the motivation for this research is focused to investigate the econometric outcomes of human, social and organizational capital on the performance of the Gulf Cooperation Council (GCC) conventional and Islamic banks.Design/methodology/approach – Design/methodology/approach The study uses a panel data analysis of Islamic and conventional banks across the GCC region. To assess these elements, the model of Value-Added Intellectual Coefficient (VAIC) was used to measure the intellectual capital and the key indicators, return on assets (ROA) along with return on equity (ROE) have been used for financial performance.Findings – The results show that the impact of intellectual capital on performance is significant for both types of banks but to a different extent. In contrast to conventional banks, human capital and structural capital have a predominant effect on Islamic banks, indicating a greater reliance on knowledge-based resources and ethical banking principles by Islamic banks. In contrast, traditional banks show a more balanced share of each component of intellectual capital. The results further indicate the instrumental importance of intellectual capital for the financial stability and operational efficiency of above mentioned banking models.Originality/value – Comparing intellectual capital management in Islamic and conventional banks in the GCC, this study provides insights for managers, policymakers and investors to improve sustainable strategies..Research Implications – This study highlights the role of intellectual capital investment in improving financial performance in both Islamic and conventional banks. The study recommends policy makers to develop regulations to promote the growth of intellectual capital, especially in Islamic banking. Future research can explore external factors such as economic conditions and technology on this relationship and extend it to other regions.